Efeito da leptospirose sobre a reprodução e a produção em rebanhos leiteiros e estimativa da herdabilidade - Pivetta, Cristian Gilberto (2009)
The objectives of this study were to evaluate the effect of Leptospirosis on reproductive and productive performance for dairy breeds cows and to identify the inheritance of this disease by estimating the coefficient of heritability. There were used 1,788 test day milk records, measured in 115 Holstein, 16 Jersey and 18 crossbred cows, daughters of 51 bulls, collected between June/2007 and February/2008 in six herds raised in the Western Region of Santa Catarina State. The file contained the following information: identification of animal (cow) and his father, date of the cow birth, date of the last delivery, test day milk production; reproductive history, Leptospirosis serology, nutrition and health management and outcome of treatment. The effect of Leptospirosis on milk production was evaluated by comparing the performance of serum positive animals, before and after the treatment, through the Test PDIFF, while the effect on the reproductive characteristics were evaluated through the test of the "Qui" Square, relating the serology for Leptospirosis and the reproductive history of animals. The Leptospirosis inheritance probability was evaluated by the coefficient of heritability for serology and for this, there were used 125 records measured in 97 Holstein, 10 Jersey and 18 crossbred cows, daughters of 27 bulls. The results of this study show that Leptospirosis causes reproductive problems, since 70.67% of the animals with positive serology for the disease showed reproductive problems such as repetition of estrus, abortion and prolonged anestrous. Leptospirosis also causes reduction in milk production, since the serum positive animals yielded an average 20.09 liters/day before being treated and, 22.01 liters/day after the treatment, difference equivalent to 1.92 liters/day. The coefficient of heritability of 36% shows that it is possible to produce a population more resistant to the disease by selection.